Co-ideation critique unfolded: an exploratory study of a co-design studio 'crit' based on the students' experience. Issue 2 (3rd April 2021) - Boudhraa, Sana; Dorta, Tomas; Milovanovic, Julie; Pierini, Davide
ABSTRACT: This article describes the effects of a co-design pedagogic strategy on students' engagement in the critique. The co-design pedagogy proposes a critique setting where students are enticed to participate in a co-design activity. We aimed to describe students' engagement in that critique setting based on two factors: how they participate in the co-ideation process based on the analysis of verbal exchange (Collaborative Ideation loops), and how they felt during the critique based on the analysis of their psychological experience state (feeling of Flow). A case study of six sessions of studio critique involving industrial design students is described. Our results show that students engage in Collaborative Ideation Loops in three different ways. Two Design Flow patterns were observed in our dataset that illustrate an association between students' experience state and specific elements of Collaborative Ideation Loops.